ANALISIS PENGARUH KINERJA KEUANGAN, MANAJEMEN RISIKO DAN MANAJEMEN MODAL KERJA TERHADAP RETURN SAHAM (Studi Kasus pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI tahun 2014-2016) - Dian Aulia Fitri; Ronny Malavia Mardani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract            This study aims to analyze the influence of financial performance with a debt to equity ratio, return on investment, current ratio, and total assets turnover, then risk management using interest rates and working capital management using the cash conversion cycle of stock returns in food companies and beverages listed on the Indonesia Stock Exchange in 2014-2016.Population and sample are companies listed on the IDX and meet the research requirements of 9 companies. Data collection is done by downloading the financial statements of each company on the IDX website. Data analysis in this research using SPSS version 19. Data testing technique used in this research include normality assumption test, classic assumption test, multiple linear regression analysis, and partial test.The results of the analysis show that partially the debt to equity ratio, return on investment, total assumption turn over and cash conversion cycle do not affect the stock returns of food and beverage companies listed on the Stock Exchange in 2014-2016. While the current ratio variable and interest rate affect the stock returns of food and beverage companies listed on the Stock Exchange in 2014-2016.Keywords: Financial Performance, Risk Management, Interest Rate